Impact of E-Service Determinants on Online Repurchase Intention of Staff of University of Maiduguri Nigeria - Saleh Audu Sani; Mohammed Dauda; Bintu Mustapha (Walidem Institute and Publishing, 2025)
Objective: This study examines the influence of reliability and ease of use on online repurchase intention among the staff of the University of Maiduguri. Theoretical Framework: Grounded in the Technology Acceptance Model (TAM) and Expectation-Confirmation Theory (ECT), the study explores how these factors shape consumer repurchase behaviour. Literature Review: Studies highlight the role of reliability and ease of use in online shopping. Reliability fosters trust and satisfaction, increasing repurchase intentions. Ease of use enhances user experience but has a debated impact on repurchase intention. Research in emerging markets emphasizes trust, website functionality, and service quality as key determinants of repurchase behaviour. However, gaps exist in understanding these factors in Nigeria’s e-commerce sector. Methods: A quantitative approach was used, with data from 436 respondents via structured questionnaires. Snowball sampling was employed, and analysis was conducted using SPSS. Results: Reliability significantly influences online repurchase intention, indicating that dependable e-commerce services encourage repeat purchases. However, ease of use and trust showed an insignificant relationship with repurchase intention. Implications: E-commerce firms should enhance reliability to build customer trust. While ease of use may not directly impact repurchase decisions, a user-friendly platform is still essential. Novelty: This study provides empirical evidence on the role of reliability and ease of use in repurchase intention in Nigeria, emphasizing the importance of reliability in e-commerce strategies. Ensuring consistent, reliable services strengthens customer loyalty. Future research should explore factors like personalized experiences and post-purchase support to further understand online repurchase behaviour.